Natumi takes the lead : the true story of an orphan elephant who finds family - Ellis, Gerry; Novesky, Amy (National Geographic Kids, 2016)
After losing her mother, shy Natumi is rescued by a team from the David Sheldrick Wildlife Trust, an orphanage for baby elephants. At the shelter, Natumi hides behind keepers' legs to watch the other elephants at the shelter. But soon, she meets several other orphans, and the eight of them play together in the surrounding bush. As the babies become closer and more like a real family, they need a leader, someone they can trust. Can Natumi grow into this role? Join the herd to find out what happens when they travel back into the wild.